Os “Manuscritos de Angelis”: uma análise sobre a alimentação no Tape (1615 -1641) - Sant’Ana , Paula de Oliveira (2022)
This dissertation sought to integrate the elements that comprised the dynamics of eating habits in the "Manuscripts of the Angelis Collection", in Tape. The first chapter is a theoretical construction about the history of food, which provides a look at the development of eating habits and how they are present in each historical context, especially in Brazilian cuisine, which appropriates various foods that are mentioned in the manuscripts. This chapter presents the Manuscripts of the de Angelis Collection, as well as Pedro de Angelis and Jaime Zuzarte Cortesão. The second chapter presents the context of the Jesuit missions, especially the Society of Jesus, which was founded by Ignácio Loyola, as well as the reduction process, aspects of the region, and the foods present in Tape. Finally, the third chapter analyzes biological, cultural, economic, philosophical, and social approaches to the role of food in the reductions. Through this analysis it is understood that food goes beyond the merely physical aspect and assumes a central role in the history of the reductions in Tape, becoming a conductor of meanings, status, and mentalities in the reductions.